Hubungan Pengetahuan Dengan Perilaku Penggunaan Alat Pelindung Diri (APD) Pada Pekerja Proyek “Mainline 1” PT. Nindya Citra Kharisma Kso Tahun 2023 - Ferlina Rizky Indah Nugroho; Anggun Nabila; Namira Wadjir Sangadji; Putri Handayani (Lembaga Pengembangan Kinerja Dosen, 2023)
Based on accident statistics data at PT. Nindya Citra Kharisma KSO, many accident cases are due to poor behavior in the use of Personal Protective Equipment (PPE) caused by low knowledge about PPE. Therefore, quantitative research was conducted on the relation of knowledge with the behavior of using Personal Protective Equipment (PPE) in workers of the